Case report: The first case of Mpox in a patient with HIV in Burundi - Doriane Sabushimike; Marc Nimburanira; Esther Freeman; Esther Freeman; Déo Simbarariye; Armel Nzeyimana; Wendemagegn Enbiale (Frontiers in Medicine)
IntroductionMpox is a viral disease that primarily affects individuals living in endemic regions. The 2022 outbreak notably impacted HIV-positive individuals, who were disproportionately affected. This report describes the first confirmed case of Mpox in Burundi, involving an HIV-positive patient with advanced disease. The case was confirmed by the national laboratory during the early stages of the 2024 outbreak.Case presentationA 50-year-old woman presented with pustular and necrotic skin lesions, vulval ulcers, and systemic symptoms. She was diagnosed with HIV upon initial evaluation and, despite an initial misdiagnosis, was ultimately confirmed to have a co-infection of Mpox. Complications included secondary bacterial infection, severe pain, and prolonged healing.ConclusionHIV coinfection can exacerbate Mpox, leading to severe clinical presentations. Therefore, early recognition and screening for HIV in Mpox patients are essential.